(untitled) - Bengtson, Vern L; Burton, Linda (New York, 1995)
Includes bibliographical references and indexes; Culture, social-structure and intergenerational role relationships : general observations and the case of Japan / Carmi Schooler -- Cultural comparison and intergenerational relations / David I. Kertzer -- Perceived family environments across generations / K. Warner Schaie and Sherry L. Willis -- Generational shifts in family environments : perceived and real? / Christopher Hertzog -- The life-course approach to perceived family environments / John C. Henretta -- The "intergenerational stake" hypothesis revisited : parent-child differences in perceptions of relationships 20 years later / Roseann Giarrusso, Michael Stallings, Vern L. Bengtson -- Wanted : alternative theory and analysis modes / Alice S. Rossi -- A finding in search of an interpretation : discussion of "The intergenerational stake hypothesis revisited" / Victor W. Marshall -- A response to Rossi / Roseann Giarrusso ... [et al.] -- Afterword : six controversies in current research on adult intergenerational relationships / Vern L. Bengtson; The demography of changing intergenerational relationships / Janice I. Farkas, Dennis P. Hogan -- Demographic influences on intergenerational relationships / Peter Uhlenberg -- Beanpole or beanstalk? Comments on "The demography of changing intergenerational relations" / Judith Treas -- Intergenerational continuity and change in rural America / Glen H. Elder, Jr., Laura Rudkin, Rand D. Conger -- Disruptive events and the life course / John Myles and Susan Morgan -- Rural families as a model for intergenerational transmission / Martin Kohli -- Intergenerational patterns of providing care in African-American families with teenage childbearers : emergent patterns in an ethnographic study / Linda M. Burton -- Intergenerational support within African-American families : concepts and methods / Linda M. Chatters and Rukmalie Jayakody -- Kindred and kin : the first and last source of support ; Kinship and individuation : cross-cultural perspectives on intergenerational relations / Christine L. Fry; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Aging; Intergenerational relations; Quan hệ giữa các thế hệ; Người lớn tuổi